Makna Cantik Dalam Drama Korea “True Beauty” (Analisis Semiotika Roland Barthes): Analisis Semiotika Roland Barthes (Universitas Merdeka Madiun, 2025)
The study is going to examine the social issues which are depicted by TV dramas from Korea depicting beauty's meaning. Researchers are able to identify signs through the scenes of a drama based on True Beauty. Roland Barthes is using the semantic theory in this case. The researcher uses a qualitative research approach with the Roland Barthes model of Semiotic analysis which divides the system of meaning into three.The first level of significance system is denotation, which means the real meaning. Second, Connotations are a secondary system of significance and dual meanings that derive from culture and experience. Third is the development of meaning through associations and explains how cultures perceive different aspects of reality. Based on the results of the analysis of scenes through the Korean drama series